ANALYZING EFFECTIVE STRATEGIES FOR TEACHING LISTENING SKILLS TO EFL STUDENTS - Putri Adelia Mado; Karmila Machmud; Nurlaila Husain (International Journal of Teaching and Learning, 2025)
The purpose of this research was to investigate the implementation of English language teaching strategies for developing listening skills in students learning English as a foreign language (EFL). A qualitative descriptive method was used in the study. In order to answer the research question, the researchers collected data from open-ended interview statements from three teachers at SMA Negeri I Paleleh. The researchers analysed the data through the process of data collection, data reduction, data display and conclusion. The findings of this research indicate that the implementation of bottom-up and top-down strategies could improve students' knowledge and listening skills. The use of bottom-up and top-down strategies helped students to improve their listening skills because learners found the strategies enjoyable and were able to share their perspectives based on their prior knowledge of the topic. In addition, teachers were able to provide students with detailed knowledge about the learning topic.